A novel classification for evaluating episiotomy practices: application to the Burgundy perinatal network - Thomas Desplanches; Emilie Szczepanski; Jonathan Cottenet; Denis Semama; Catherine Quantin; Paul Sagot (BMC, 2019)
Abstract Background Though the rate of episiotomy has decreased in France, the overall episiotomy rate was 20% in the 2016 national perinatal survey. We aimed to develop a classification to facilitate the analysis of episiotomy practices and to evaluate whether episiotomy is associated with a reduction in the rate of obstetric anal sphincter injuries (OASIS) for each subgroup. Methods This population-based study included all the deliveries that occurred in the Burgundy Perinatal Network from 2011 to 2016. The main outcome was episiotomy, which was identified thanks to the French Common Classification of Medical Procedures. An ascending hierarchical cluster analysis was performed to build the classification. A clinical audit using the classification was conducted yearly in all obstetric units. The episiotomy rates were described throughout the study period for each subgroup of the classification. The OASIS rates were evaluated by subgroup and the association between mediolateral episiotomy and OASIS was investigated for each subgroup. Results Our analyses included 81,290 pregnant women. The classification comprised 7 subgroups: (1) nulliparous single cephalic at term, (2) nulliparous single cephalic at term with instrumental delivery, (3) multiparous single cephalic at term, (4) multiparous single cephalic at term with instrumental delivery, (5) all preterm deliveries (< 37 weeks gestation), (6) all breech deliveries, (7) all multiple deliveries. Episiotomy rates ranged from 6.2% in Group 3 to 40.9% in Group 2. From 2011 to 2016, every group except breech deliveries experienced a significant decrease in episiotomy rates, ranging from − 28.1 to − 61.0%. The prevalence of OASIS was the highest in Groups 2 (3.0%) and 4 (2.2%). Overall OASIS rates did not significantly differ with episiotomy use (P = 0.25). However, we found that the use of episiotomy was associated with a reduction in OASIS rates in Groups 1 and 2 (odds ratio 0.6 [95% CI 0.4-0.9] and 0.4 [0.3-0.5], respectively). This reduction was only observed in Group 4 with forceps delivery (odds ratio 0.4 [0.1-0.9]). Conclusion We developed the first classification for the evaluation of episiotomy practices based on 7 clinically relevant subgroups. This easy-to-use tool can help obstetricians and midwives improve their practices through self-assessment.